Interactions between white pine blister rust, bark beetles, and climate over time indicate vulnerabilities to limber pine health - Burns, Kelly S.; Tinkham, Wade T.; Leddy, K. A.; Schoettle, Anna W.; Jacobi, William R.; Stewart, Jane E. (Frontiers in Forests and Global Change, 2023)
Introduction Limber pine is a keystone species in the Rocky Mountains that grows on harsh, high elevation sites where few other tree species can. Recent studies suggest the species is threatened by the combined impacts of the exotic, invasive disease, white pine blister rust (WPBR), native bark beetles, and climate change. Information on changes in the health of limber pine populations and long-term impacts posed by these threats is needed to inform management efforts. Methods We established 106 long-term monitoring plots in 10 study areas that were surveyed three times between 2004 and 2017. We assessed site and stand factors, tree health, and regeneration over time to detect changes in limber pine abundance and health, cumulative impacts of WPBR and bark beetles, and to evaluate the drivers of WPBR occurrence and severity. Results Limber pine health declined significantly over the study with more than 20% of initially live limber pine trees dead by the last measurement cycle, primarily due to WPBR and bark beetles. While some recruitment occurred, mortality rates greatly outpaced recruitment of ingrowth. Disease incidence and how it changed over time was variable, but disease severity increased substantially overall and in all study areas. Limber pine regeneration was low or absent in most sites and mortality caused by WPBR increased significantly. We found strong relationships between WPBR and aridity. Trees in habitats with high vapor pressure deficit were less likely to be infected with WPBR, but trees that were already infected were more likely to develop severe symptoms and die. Longer growing seasons increased the likelihood of WPBR presence and mortality. Growing season length and vapor pressure deficit tended to increase over the study, suggesting that climate change may exacerbate disease impacts. Discussion Declining health of limber pine coupled with high mortality rates, increasing disease severity, and low levels of natural regeneration indicate successful recovery may not occur in some locations without management intervention. Proactive management strategies to reduce insect and disease impacts and promote stand recovery and resilience should be pursued in remaining, healthy limber pine ecosystems.